Effectiveness of Ecological Management to Support Reclamation on Tails Land at The Milepost 21 Reclamation and Biodiversity Research Center Based on Environmental Policy - Yoom, Lilis Irjayanti; Chaerul, Muhammad; Desi, Natsar (Journal La Lifesci, 2025)
This study investigates the effectiveness of ecological management in supporting reclamation of tailings land at the Mile Post 21 Reclamation and Biodiversity Research Center, PT Freeport Indonesia. Using a qualitative descriptive approach, the research employs primary data obtained through interviews, documentation, and direct observation, complemented by secondary data from archives, reports, and company records. The analysis is guided by ISO 14001 environmental management principles, using a checklist method adapted from the Global Environmental Management Initiative (GEMI) to evaluate ecological, technical, socio-economic, and regulatory aspects of reclamation practices. Findings reveal that ecological management at Mile Post 21 has been highly effective, achieving more than 80% compliance with ISO 14001 indicators. Vegetation cover increased from less than 10% to over 75%, with more than 160 planted species complemented by natural succession involving over 500 species. Soil quality improved significantly, with organic carbon rising from <0.5% to 2.5%, pH levels increasing toward neutrality, and cation exchange capacity reaching medium–high levels. These changes facilitated the restoration of ecological functions and supported biodiversity recovery. Moreover, reclaimed land has been transformed into productive agricultural areas integrating crops, livestock, and aquaculture, providing socio-economic benefits for local communities and involving indigenous landowners in sustainable management. Despite technical challenges related to poor soil properties and managerial constraints such as long-term funding, the program demonstrates that ecological management, when implemented systematically under ISO 14001, can effectively restore degraded post-mining land into ecologically resilient and socially beneficial systems.